Eros e Tânatos nos meios de comunicação de massa e na Web 2.0: a pulsão de integração e confiança no website CouchSurfing - Branda Junior, Newton de Andrade (2010)
The aim of this research is to analyze the construction that allows a greater prevalence of the integration, acceptance and trust drives (eros) at the CouchSurfing website, which is a digital organization that allows free hosting for people worldwide in the homes of its users. Thus, two psychoanalysis concepts will be used eros and thanatos taking into account their expansion to a regional and current context. These concepts were originally formulated by Sigmund Freud in Beyond the Pleasure Principle (1996) and Civilization and its Discontents (2006). The following pieces will also be used and placed to engage concepts: Paradoxical Logic, presented in the book The Vision Machine (2002), from Paul Virilio; Umwelt, by the German biologist Jakob von Uexküll, from a text by Thure von Uexküll published in Galaxy magazine, # 7 (2004); and Mass, by the French philosopher Jean Baudrillard, in In the Shadow of Silent Majorities (2004). As well as the concepts of Collective Intelligence, by Pierre Lévy; The Wisdom of Crowds, by James Surowiecki; and Emergence, by Steve Johnson, published respectively in books with the same name and finally, Social Logic, by the researcher Alan Zuckerman, in The Social Logic of Politics (2005). Within all these theoretical basis, it will be identified which specific strategies of this community website lead many of its users to enhance the erotic impulse of cooperation, trust and care to the point of opening their homes to host complete strangers. Therefore, an analysis of the community website ways of attraction and operation was made in the sense of identifying which communications logic ultimately generates such trust. Through hypotheses, it is believed that the possibility of disengagement whenever needed is a crucial factor in helping availability. The fact that digital communication allows the expression of the natural instinct for socialization, now constrained by much of the mass media fear prioritization (thanatos) has also been taken into account in this study. Another assumption is that the CouchSurfing enables choice. The user, within his or her personal expectations, defines lasting and relationship intensity options during accommodation. This study relevance is in understanding how some mass communication vehicles mostly encourage fear among one another while the new communication vehicles (the digital media or the new media ) enable the flow of the need for belonging and encourage community collaborative actions. These study findings may offer the possibility of a more critical understanding of communication strategies used by digital media